ANALISIS HUBUNGAN GAYA KEPEMIMPINAN DAN LOYALITAS DENGAN KINERJA KARYAWAN PADA BENGKEL MOBIL REWWIN MOTOR SERVICE - Abidin, Muhammad Zainul; Lestari, Sri (Transpublika Publisher, 2022)
This study aims to determine the analysis of the relationship between leadership style and loyalty with employee performance at the Rewwin Motor service car workshop. The method used is a qualitative method, a descriptive study of the qualitative aims to describe the image of the object being examined, such as without analyzing and making conclusions. The population of this study were 30 informants. Sampling used saturated sampling, where the entire population was used as a sample to test as many as 30 informants. Research data collection was done through interviews and questionnaires. Interviews were conducted using a data questionnaire consisting of data related to the questions needed to achieve the research objectives. Questionnaires were prepared by distributing questionnaires containing questions to Rewwin Workshop employees. The average shows different variables, indicating that more colleagues affect work relations in employee performance because co-worker relations or a group of employees utilize and create quality employee communication, employee discipline orientation produces a healthy working atmosphere and increases efficiency productivity.